3D localization of cytoskeleton in mouse spermatids using stochastic optical reconstruction microscopy - Sunny, Reshma, author; Krapf, Diego, advisor; Nikdast, Mahdi, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2022)
It is estimated by the World Health Organization that globally 186 million individuals live with infertility. Studies have shown that cause of male infertility is unknown in 30 to 50% of the cases. Over the last several years teratozoospermias have been investigated and have been backtracked to events in spermatogenesis. The development of the acrosome and the manchette, protein and vesicle transport in spermatids, and sperm head shaping are crucial steps in the formation of healthy sperms. The cytoskeleton in spermatids plays a crucial role in shaping the sperm head. The acroplaxome exerts forces on the nucleus and gives the mammalian sperm head its species-specific shape, and also facilitates the proper attachment of the nuclear cap called the acrosome, containing the enzymes required for sperm penetration of the oocyte. The manchette should be intact and formed properly to have shortened diameter as spermatids differentiate so that it can constrict the base of the nucleus to shape the head, and also facilitate the transport of cargo to the base of the cell. Thus as studies have confirmed, the disruption in the organization of the cytoskeleton is a concern for infertility. Hence it is crucial to learn more about the cytoskeletal structures in spermatids. The goal of this thesis is to 3D localize these structures. The major structures we are interested in are the acroplaxome and the manchette. For this, we use a super-resolution microscopy method called Stochastic Optical Reconstruction Microscopy to image spermatid cytoskeleton. Our experiments confirmed the presence of α-tubulin in the manchette and that of F-actin in the manchette and the acroplaxome, as previously observed by researchers with 2D confocal images. We observed that the manchette reduces in diameter and progresses to the caudal portion of the cell at the later steps of differentiation and that the structure forms completely at step 10 and disassembles after step 14.